2008
DOI: 10.1111/1524-4725.2006.32029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect of a Single Pulsed Dye Laser Treatment of Fresh Surgical Scars: Randomized Controlled Trial

Abstract: A single pulsed dye laser treatment at the time of suture removal does not appear to have a beneficial effect on clinical scar appearance. The point of minimal benefit for such laser treatments may lie somewhere between one and three treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…Redness and telangiectasia developing in such scars usually spontaneously remit, but often slowly and incompletely. Laser can not only accelerate this decolorizing process, it can also advance the end point closer to the complete absence of redness with improvement in scar texture and pliability with minimal side effects [2]. Recently, Capon et al [3] showed the ability of a 815-nm diode-laser system to assist wound closure leading to an acceleration and an improvement of wound healing with indiscernible resulting scar in hairless rats.…”
mentioning
confidence: 99%
“…Redness and telangiectasia developing in such scars usually spontaneously remit, but often slowly and incompletely. Laser can not only accelerate this decolorizing process, it can also advance the end point closer to the complete absence of redness with improvement in scar texture and pliability with minimal side effects [2]. Recently, Capon et al [3] showed the ability of a 815-nm diode-laser system to assist wound closure leading to an acceleration and an improvement of wound healing with indiscernible resulting scar in hairless rats.…”
mentioning
confidence: 99%
“…Similar to this study, clinical investigations of early laser treatment to reduce scar formation have previously used single laser exposure of various types. 12 Under these conditions, slight laser-mediated improvement of treated scars has been reported. In accordance with previous results, subtle differences were visualized in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, these studies report improved subsequent scar appearance. 11,12 Only Hong et al 13 investigated the appropriate timing of laser intervention to reduce scarring. This study shows that the use of early fractional CO2 lasers 4 weeks after surgery or trauma is an effective and safe method to minimize scar formation, 13 substantiating the concept of "the earlier the treatment, the better."…”
Section: Discussionmentioning
confidence: 99%
“…Many pioneering studies on PDL therapy has been focused on incisional scars [8][9][10][11][12][13][14][15][16]. While the results have been generally positive, several centers have found less than enthusiastic results [17][18][19][20][21]. As an example, no difference in erythema was found in a prospective randomized controlled study on the effect of PDL on surgical hypertrophic scars in a cohort of 19 patients with average scar duration of 32 months [18].…”
Section: Introductionmentioning
confidence: 99%